HUBUNGAN ANTARA SARAPAN PAGI DENGAN TINGKAT KONSENTRASI BELAJAR SISWA - Moh. Zainul Ma'arif; Alifea Meta Duwairoh; Arisa Septianingrum Firdauz (Jurnal Penelitian, 2021)
The results of the 2018 Program for International Student Assessment (PISA) survey show that Indonesian student achievement is ranked 74th out of 79 countries. Indonesia's score is still low. Learning achievement is closely related to learning concentration. One of the effects of learning concentration is the calories of breakfast in the morning, because a breakfast with sufficient calories can meet the body's needs so that the body can continue to optimize metabolism as fuel for the brain to work. The purpose of this study was to determine the relationship between breakfast and the level of concentration in student learning.This study uses a correlational analytical design with a cross sectional time approach. A sample of 40 respondents was taken by simple random sampling. Data was taken by using observation. While the statistical test used is the Spearman's Test.The results showed that as many as 20 students (50%) had breakfast in accordance with the standard needs and had a good concentration of learning as many as 19 students (47.5%). The results of the Spearman's test show that there is a relationship between breakfast and the concentration level of students' learning (p value = 0.000). The conclusion that breakfast affects learning concentration. Breakfast must meet the daily nutritional needs of 30% of the total calorie needs.